Pharmacologically Active Secondary Metabolites from Psoralea corylifolia - Ni Putu Ariantari; Elizabeth S. P. Ratnasantasyacitta (Journal of Tropical Pharmacy and Chemistry, 2022)
Psoralea corylifolia has gained much attention, particularly in the cosmetic industry for the past few years owing to promising pharmacological activities of its metabolites. Seeds of P. corylifolia are the main source of bakuchiol, a meroterpene compound that is extensively harnessed in numerous skincare products. Furanocoumarins, psoralen and isopsoralen are other metabolites mainly from P. corylifolia seeds and known for their antipsoriatic activity. Moreover, various studies have reported several classes of secondary metabolites from this plant possessing diverse biological activities. This article highlights recent updates on P. corylifolia phytoconstituents and their promising pharmacological activities based on scientific publications during the last 10 years (2011-2021). The literature search was carried out through scientific-based websites and databases such as Google Scholar, NCBI, and PubMed. This paper included sixty-three bioactive metabolites reported in the last 10 years, belonging to the group of flavonoids, meroterpenes, furanocoumarins, coumestans, steroid and phenolic compounds. These phytoconstituents displayed a broad range of bioactivities including anti-inflammatory, antibacterial, antidiabetic, controlling obesity, hepatoprotective and cytotoxicity. Keywords: Bakuchiol, pharmacological activities, Psoralea corylifolia, bioactive metabolites.